Peran Kewirausahaan Perempuan, Kewirausahawan Ramah Lingkungan Dan Orientasi Pasar Sebagai Variabel Yang Mempengaruhi Kinerja Pemasaran UMKM - Octavia, Ade; Sriayudha, Yayuk; Zulfanetti (Jurnal Samudra Ekonomi dan Bisnis, 2023)
Women play an important role in the field of entrepreneurship in the small and medium industry. This study aims to analyze the role of women entrepreneurship, eco-friendly entrepreneurship, and market orientation, on the marketing performance of SMEs. This quantitative research uses a sample survey where the number of respondents is 200 people. Primary data was collected through a questionnaire with a 5-Likert scale. Data analysis using SEM-PLS. Research findings show that women's entrepreneurship has a significant effect on eco-friendly entrepreneurship, as well as market orientation. In addition, environmentally friendly entrepreneurship has been proven to have a significant effect on market orientation, and market orientation has been proven to have an effect on marketing performance. Simultaneously, the marketing performance of MSMEs is significantly influenced by women entrepreneurship, eco-friendly entrepreneurship and market orientation.